Toll‐like receptor 3 activation modulates hippocampal network excitability, via glial production of interferon‐β. Issue 8 (3rd June 2013) - Costello, Derek A.; Lynch, Marina A.
ABSTRACT The family of toll‐like receptors (TLR) plays a major role in innate immunity due to their pathogen‐recognition abilities. TLR3 is a sensor for double‐stranded RNA, and regulates host‐defense responses to several viruses, via the production of type I interferons. Interferon‐β (IFNβ) is a primary product of TLR3 activation, and its transcription is elevated in the CNS response to the synthetic TLR3 ligand, polyinosinic‐polycytidylic acid (poly(I:C)). Peripheral infections, along with TLR‐induced inflammatory mediators, are known to have detrimental effects on brain function, exerting a negative impact on cognition and enhancing seizure susceptibility. In this study, we assessed hippocampal function in vitro, in response to systemic delivery of a TLR3 agonist. Unlike agonists of other TLRs, intraperitoneal injection of poly(I:C) did not adversely affect evoked short‐ and long‐term synaptic plasticity in mouse hippocampal slices. However, sustained and interictal‐like spontaneous activity was observed in CA1 pyramidal cells in response to poly(I:C) and this was associated with alterations in the expression of phosphorylated NR2B subunit‐containing NMDA receptors and an astrocyte‐specific glutamate/aspartate transporter (GLAST) which impact on extracellular glutamate concentration and contribute to the genesis of epileptiform activity. We provide evidence for the production of IFNβ from microglia and astrocytes, and using mice deficient in the type I IFN receptor α 1 (IFNAR1), demonstrate that its subsequent activation is likely to underlie the TLR3‐mediated modulation of hippocampal excitability. © 2013 Wiley Periodicals, Inc.